Isolation and transformation of perennial ryegrass (Lolium perenne L.) protoplasts for the in vivo assessment of guide RNAs editing efficiency - Sustek-Sánchez, Ferenz; Eelmets, Erki; Nigul, Lenne; Kärblane, Kairi; Laasmaa, Martin; Balode-Sausina, Madara; Berzina, Sanda Astra; Ducis, Davis; Kaktina, Elza; Jaškūne, Kristina; Rognli, Odd Arne; Rostoks, Nils; et al. (Frontiers in Plant Science, 2026)
Protoplasts are broadly used to perform different cellular and genetic assays. Transformation of protoplasts requires isolation methods that generate a large number of intact cells suitable for downstream applications. Lolium perenne L. is an important forage grass species for which gene editing techniques are in their early stages. Using protoplasts has previously been reported as a suitable approach to test the genome editing efficiency of guide RNAs in important grass species like wheat and rice. This approach can speed up and increase the chances of generating edited plants, especially when working with species for which stable transformation methods have not been established yet. Testing two different approaches regarding the processing of L. perenne L. tillers showed that using a blender for disintegrating the tissue was easier and faster than cutting the tillers with a razor blade. Conversely, the more classical strategy (cutting with a razor) provided a higher number of viable protoplasts. The use of an enzyme solution containing 2% cellulase during 8 h was shown to be the best experimental condition for protoplast isolation. The addition of a sucrose cushion improved the purification of alive cells, which were then positively transformed with guide RNA encoding vectors using polyethylene glycol. The presence of indels induced by these vectors was then confirmed through decomposition-based analysis of their sequenced genomic DNA. These results demonstrated the suitability of using protoplasts for the in vivo assessment of guide RNAs editing efficiency.